Current Control and Active Damping for Single Phase LCL-Filtered Grid Connected Inverter - Mohammad Alshiekh; Alaa Marouf; Muhieddin Kubeitari (Journal of Control Science and Engineering)
LCL filter has been widely used in the grid connected inverter, since it is effective in attenuation of the switching frequency harmonics in the inverter. However, the resonance in this filter causes stability problems and must be damped effectively to achieve stability. There are some methods to damp the resonance; one method is passive damping of resonance by adding a series resistor with the filter capacitor, but passive element reduces the inverter efficiency. Other method uses active damping (AD) by adding a proportional control loop of filter capacitor current, but this method needs additional sensor to measure filter capacitor current; moreover, when the control loops are digitally implemented, the computation delay in AD control loop will lead to some difficulties in choosing control parameters and maintaining system stability. This paper presents current control scheme for the grid connected inverter with the LCL filter. The proposed scheme ensures the control of injected current into grid with AD of the resonance in the LCL filter while keeping system stability and eliminating the effect of computation delay of the AD loop. An estimation of filter capacitor current with one step ahead is performed using the discrete time observer based on measuring the injected current. This reduces the cost and increases the robustness of the system. Proportional Resonant (PR) controller is used to control the injected current. Design of control system and choosing its parameters are studied and justified in details to ensure suitable performance with adequate stability margins. Simulation and experimental results show the effectiveness and the robustness of the proposed control scheme.